2020
DOI: 10.1002/anie.202004762
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Imaging of the Tumor‐Associated Enzyme NCEH1 with a Covalent PET Probe

Abstract: Herein, we report the development of an 18F‐labeled, activity‐based small‐molecule probe targeting the cancer‐associated serine hydrolase NCEH1. We undertook a focused medicinal chemistry campaign to simultaneously preserve potent and specific NCEH1 labeling in live cells and animals, while permitting facile 18F radionuclide incorporation required for PET imaging. The resulting molecule, [18F]JW199, labels active NCEH1 in live cells at nanomolar concentrations and greater than 1000‐fold selectivity relative to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…Using covalent PET probe imaging, they observed that NCEH1 was primarily localized to the outer edges of xenograft tissues, with less localization within the tumor. These results indicate that NCEH1 may contribute to the aggressiveness and metastasis of breast cancer cells 21 . By hydrolyzing the metabolic intermediate, 2‐acetylmonoalkylglycerol, NCEH1 may regulate the ether lipid signaling network that links platelet activating factor and lysophosphatidic acid metabolism.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Using covalent PET probe imaging, they observed that NCEH1 was primarily localized to the outer edges of xenograft tissues, with less localization within the tumor. These results indicate that NCEH1 may contribute to the aggressiveness and metastasis of breast cancer cells 21 . By hydrolyzing the metabolic intermediate, 2‐acetylmonoalkylglycerol, NCEH1 may regulate the ether lipid signaling network that links platelet activating factor and lysophosphatidic acid metabolism.…”
Section: Discussionmentioning
confidence: 91%
“…Neutral cholesterol ester hydrolase 1 (NCEH1), also known as arylacetamide deacetylase‐like 1 (AADACL1) and KIAA1363, is a serine hydrolase, which has diverse biological activities and cellular functions 20‐24 . NCEH1 hydrolyzes cholesterol esters to free cholesterol, which contributes to the development of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This probe activity showed the promising activity on blocking profibrotic response in idiopathic pulmonary fibrosis [ 27 ]. Another 18F-labeled, activity-based probe ([18F]JW199) was developed to target the cancer-associated serine hydrolase NCEH1, particularly in triple-negative breast cancer [ 28 ].…”
Section: Hydrolase Activity Probementioning
confidence: 99%
“…An elevated NCEH1 activity increases hydrolysis of cholesterol esters, and knockdown of NCEH1 logically induces elevated cholesterol ester levels [93,94]. Expression of NCEH1 is ubiquitous throughout the human body [95]. While a strong connection between NCEH1 and lung cancer has not been established yet, its overexpression has been linked to many cancer types including ovarian [96] and breast [97] cancers.…”
Section: Neutral Cholesterol Ester Transferase 1 (Nceh1)mentioning
confidence: 99%